2014
DOI: 10.1093/aje/kwt446
|View full text |Cite
|
Sign up to set email alerts
|

The Contributions of Solar Ultraviolet Radiation Exposure and Other Determinants to Serum 25-Hydroxyvitamin D Concentrations in Australian Adults: The AusD Study

Abstract: The Quantitative Assessment of Solar UV [ultraviolet] Exposure for Vitamin D Synthesis in Australian Adults (AusD) Study aimed to better define the relationship between sun exposure and serum 25-hydroxyvitamin D (25(OH)D) concentration. Cross-sectional data were collected between May 2009 and December 2010 from 1,002 participants aged 18-75 years in 4 Australian sites spanning 24° of latitude. Participants completed the following: 1) questionnaires on sun exposure, dietary vitamin D intake, and vitamin D suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
87
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(94 citation statements)
references
References 38 publications
6
87
0
1
Order By: Relevance
“…These results suggest that modifiable factors related to sun exposure could help maintain the healthy state of vitamin D, such as decreased clothing coverage, rather than increasing the duration of exposure to ultraviolet rays. 43 Van den Heuvel et al evaluated the contribution of different physical activity characteristics, such as duration, intensity and location, in relation to plasma levels of vitamin D and concluded that physical activity performed at high intensity had the strongest positive association with vitamin D levels. 44 It is important to emphasize that exposure of the body to the sun during physical activity should have some particularities in order to raise the plasma concentrations of vitamin D, since it depends on the amount of melanin present in the skin, the type of clothing and the use of sunscreen, as well as hour of the day, season of the year, latitude of the place and age of the individual.…”
Section: Figurementioning
confidence: 99%
“…These results suggest that modifiable factors related to sun exposure could help maintain the healthy state of vitamin D, such as decreased clothing coverage, rather than increasing the duration of exposure to ultraviolet rays. 43 Van den Heuvel et al evaluated the contribution of different physical activity characteristics, such as duration, intensity and location, in relation to plasma levels of vitamin D and concluded that physical activity performed at high intensity had the strongest positive association with vitamin D levels. 44 It is important to emphasize that exposure of the body to the sun during physical activity should have some particularities in order to raise the plasma concentrations of vitamin D, since it depends on the amount of melanin present in the skin, the type of clothing and the use of sunscreen, as well as hour of the day, season of the year, latitude of the place and age of the individual.…”
Section: Figurementioning
confidence: 99%
“…20 In addition to body weight and skin color, other determinants of vitamin D status include season, sunlight intensity and exposure, and use of vitamin D supplements. [21][22][23][24] Research suggests that low vitamin D in obese women is not caused by reduced sun exposure. 25 In addition, US health professionals consider age to be the primary determinant of vitamin D status.…”
Section: Figure 1 Probability Of Vitamin D Deficiency By Body Weightmentioning
confidence: 99%
“…Follow-up was during the winter months, from May to October 2012, much of which is when ambient UV is too low to generate vitamin D [7].…”
Section: Methodsmentioning
confidence: 99%
“…In persons who are vitamin D deficient, as occurs in winter at high latitudes and year-round for long-term medical inpatients [6,7], there is a potential for significant dysfunction in the innate immune response, leading to a greater frequency of infections.…”
Section: Introductionmentioning
confidence: 99%